Investigation on the stress-strain relationship of rubberized concrete under uniaxial compression - Jianfan Wang (Materials Research Express)
As urbanization progresses rapidly, addressing the disposal of waste tires has become an urgent global environmental concern. This research comprehensively examined how varying rubber proportions and particle dimensions impact the workability, axial compressive stress–strain response, splitting tensile resistance, and flexural capabilities of concrete, utilizing both experimental methods and theoretical assessments. Additionally, the energy dissipation properties of rubber-enriched concrete utilizing a toughness index and developed an analytical framework to predict the compressive stress–strain relationship in rubber-modified concrete were evaluated. When the rubber content was increased to 20%, it was observed that rubber reduced the workability and load-bearing capacity of concrete, with reductions of 44.7%, 26.9% and 30.5% in slump, peak stress and modulus of elasticity, respectively. The incorporation of rubber increased the peak strain of concrete, with the maximum increase reaching 26.2%. The ultimate deflection increased by about 8.0%. Meanwhile, the toughness index was found to increase, with an increase of about 36.8%. The established stress–strain analytical model can accurately predict the stress–strain behavior of rubberized concrete under axial compression. In summary, rubberized concrete shows significant potential in enhancing seismic performance in earthquake-prone regions, optimizing structural design, and addressing environmental issues related to waste tire disposal, aligning with sustainable development goals.